Analysis of Palm Oil Production Planning for Biodiesel Needs in North Sumatra - Azura, Silva; Husein, Ismail (Sinkron : jurnal dan penelitian teknik informatika, 2024)
Palm oil has become a leading product in the plantation business in Indonesia. Currently, Indonesia has become the country with the largest palm oil production capacity in the world. With this production capability, the opportunity to diversify energy made from palm oil is very possible. The analysis of this study was carried out using secondary data to find out the extent of the potential of palm oil as the main source of biodiesel raw materials in Indonesia. The results of the analysis state that with the production and expansion of oil palm land very massive, energy diversification is a relevant step and very feasible. The role of the government through the export levy tariff policy also determines palm oil consumption for the benefit of the domestic market.